PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO (KEKUATAN DUA KEPALA) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN KELAS XI SMA NEGERI 10 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack : the research aims to knowing influence of application active learning strategy types The Power Of Two to increase student achievement in class XI IPA at SMAN 10 Pekanbaru. This study is a quasi-experiment design with randomized group pretest-posttest. The subjects were two classes that have been randomly after test of normality and homogeneity test to grade XI 5 as experiment class and class XI IPA 3 as the control class. Experiment class using of application active learning strategy types The Power Of Two. Data analysis technique used is a t-test. Based on the final results of processing the data tobtained >ttabel is 2,23>1,67 means the application of active learning strategies The Power Of Two types can improve student achievement on the subject of the solubility and solubility product in class XI IPA at SMAN10 Pekanbaru.KeyWords : the power of two, academic achievement, solubility and solubility product.